Lecture notes. - Ellis, Harold; Calne, Roy Yorke; Watson, Christopher J. E. (Christopher John Edward) (Blackwell Pub., 2011)
The 12th edition of General Surgery Lecture Notes introduces the student to the principles of common surgical operations and systematically covers all clinical problems where surgical intervention is indicated. Now in full colour throughout and fully-supported by a website of self-assessment questions and answers, this popular and classic text will appeal to all medical students and junior doctors who want a concise introduction to the fundamental aspects of general surgery and will provide the core knowledge needed for Finals and the MRCS examination